MatGeom: A toolbox for geometry processing with MATLAB - David Legland (SoftwareX)
MatGeom (for “MATLAB Geometry”) is a pure MATLAB library for geometry processing in two and three dimensions, that aims at facilitating the processing and analysis of scientific data. It provides a collection of functions for the manipulation of common 2D and 3D geometries such as points, lines, ellipses, polygons, or polygon meshes. Functions allow for combining together geometries (intersections, mutual distances, projections, fitting to a set of points), evaluating quantitative features (area, volume, curvatures, orientations), or drawing with various options. The library is fully documented: user manual, code comments, function headers, and demonstration scripts.